Antibacterial Activity of Alkaloid, Flavonoids and Lipids from Crude Extracts of Azadirachta indica on Some Selected Medically Important Bacteria - Bappah, Adamu Maryam; Qossim, Muthasir; Dambam, Zakari Nusayba; Usman, Adamu Shehu; Awalu, Uba (Journal of Biochemistry, Microbiology and Biotechnology, 2022)
Most tropical climates are home to the green perennial tree Azadirachta indica, which belongs to the Meliaceae family of Mahogany, and has long been known to have therapeutic effects. Secondary metabolites in plants cause biological activity in both humans and animals, which explains why they are used as herbs. For the investigation of the lipid, alkaloids, and flavonoids present in the A. indica extracts, thin-layer chromatography was carried out using several solvent systems. The thin layer chromatography-separated active components were tested for antibacterial efficacy against three multi-drug resistance pathogens namely: Salmonella typhi, P. aeruginosa and S. aureus. Alkaloids showed the highest antibacterial activity on Salmonella spp. (15 mm) and 12 mm Staphylococcus aureus isolates while lipids showed the least activity on the tested isolates. The minimum bactericidal concentration (MBC) and minimum inhibitory concentration (MIC) were calculated. The outcomes of the MIC and MBC revealed that the inhibitory concentrations of different plant extracts for certain bacteria varied. Values of MIC for Salmonella typhi were found in the range of 25 to 50 mg/mL, MBC 100 to 200 mg/mL and for Staphylococcus aureus MIC values ranged between 50 and 200 mg/mL, MBC 100 to 400 mg/mL and for Pseudomonas aeruginosa MIC values were found in the range of 100 to 200 mg/mL and MIC values ranged between 200 and 400 mg/mL using a different part of the plant extracted using three different solvents. The finding suggests that crude extract of A. indica might work well for the treatment of illnesses brought on by these microbes and that the activity of the crude extract is more than that of an individual component.